DAPSA GEMINA AUDISIO & DE BIASE, 1996, A NEW SPECIES OF THE EUROPEAN FAUNA (Coleoptera, Endomychidae) - Audisio, Paolo; Ruzzante, Gianpaolo; Leo, Piero (Fragmenta entomologica, 2011)
During entomological research carried out in the Pontine Islands (central Italy, Latium, Latina province), Dapsa gemina Audisio & De Biase, 1996 (Coleoptera, Endomychidae), previously known only from coastal areas of NE Algeria, has been recorded in Italy and in Europe for the first time. This new record suggested the authors to shortly discuss the possible scenario of a relatively recent, late Pleistocene passive transportation of Dapsa gemina and of the related D. obscurissima Pic, 1904 (sharing a very similar disjunct geographic distribution) by marine drift of masses of vegetal debris from North Africa.